The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1111/j.1471-4159.1992.tb09276.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Multiple‐Site Phosphorylation of Tyrosine Hydroxylase in Perfused Rat Adrenal Glands

Abstract: Tryptic digestion of tyrosine hydroxylase (TH) isolated from rat adrenal glands labeled with 32Pi produced five phosphopeptides. Based on the correspondence of these phosphopeptides with those identified in TH from rat pheochromocytoma cells, four phosphorylation sites (Ser8, Ser19, Ser31, and Ser40) were inferred. Field stimulation of the splanchnic nerves at either 1 or 10 Hz (300 pulses) increased 32P incorporation into TH. At 10 Hz, the phosphorylation of Ser19 and Ser40 was increased, whereas at 1 Hz, Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
77
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 40 publications
0
77
1
Order By: Relevance
“…However, stimulation of rat PC12 cells for only 10-15 min with NGF [2] or phorbol esters [55] caused a relatively selective increase in the 32P-labelling of Ser3 1 (about threefold), suggesting that these agonists may only increase Ser4O phosphorylation after more prolonged stimulation. Stimulation of perfused rat adrenal glands for 3 min with nicotine increased the "P-labelling of Serl9 (5.8-fold), Ser31 (50%) and Ser4O (60%), while stimulation for 3 min with muscarine increased the 32P-labelling of these three sites by 3.7-fold, 4.3-fold and 40%, respectively [53]. Electrical stimulation of the medial forebrain bundle (containing the afferent dopaminergic fibres) for 20 niin increased the phosphorylation of Ser19 (2.4-fold), Ser31 (1 .%fold) and Ser40 (1.9-fold) [9], while stimulation of the splanchnic nerves (1 Hz for 5 min) increased the "P-labeling of Serl9 (3.2-fold), Ser31 (3.7-fold) and Ser40 (4.3-fold) 191.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, stimulation of rat PC12 cells for only 10-15 min with NGF [2] or phorbol esters [55] caused a relatively selective increase in the 32P-labelling of Ser3 1 (about threefold), suggesting that these agonists may only increase Ser4O phosphorylation after more prolonged stimulation. Stimulation of perfused rat adrenal glands for 3 min with nicotine increased the "P-labelling of Serl9 (5.8-fold), Ser31 (50%) and Ser4O (60%), while stimulation for 3 min with muscarine increased the 32P-labelling of these three sites by 3.7-fold, 4.3-fold and 40%, respectively [53]. Electrical stimulation of the medial forebrain bundle (containing the afferent dopaminergic fibres) for 20 niin increased the phosphorylation of Ser19 (2.4-fold), Ser31 (1 .%fold) and Ser40 (1.9-fold) [9], while stimulation of the splanchnic nerves (1 Hz for 5 min) increased the "P-labeling of Serl9 (3.2-fold), Ser31 (3.7-fold) and Ser40 (4.3-fold) 191.…”
Section: Discussionmentioning
confidence: 96%
“…Stimulation of perfused rat adrenal glands for 3 min with nicotine increased the "P-labelling of Serl9 (5.8-fold), Ser31 (50%) and Ser4O (60%), while stimulation for 3 min with muscarine increased the 32P-labelling of these three sites by 3.7-fold, 4.3-fold and 40%, respectively [53]. Electrical stimulation of the medial forebrain bundle (containing the afferent dopaminergic fibres) for 20 niin increased the phosphorylation of Ser19 (2.4-fold), Ser31 (1 .%fold) and Ser40 (1.9-fold) [9], while stimulation of the splanchnic nerves (1 Hz for 5 min) increased the "P-labeling of Serl9 (3.2-fold), Ser31 (3.7-fold) and Ser40 (4.3-fold) 191. MAP kinase is presumably responsible for the phosphorylation of Ser3 1 in vivo, and MAPKAP kinases-1 andlor 2 are candidates for the enzymes that phosphorylate Serl9 and Ser40 under these conditions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Extensive work by many groups has shown that TH is phosphorylated by several multifunctional protein kinases [Z - 4,14,29]. The phosphorylation of Ser40 by CAMP-dependent protein kinase is by far the best characterized, and it is well established that this phosphorylation causes an activation of the bovine and rat enzymes [4,14,29,301. Kecently, it has also been found that phosphorylation of this amino acid in hTHl and hTH2 results in an activation of both isozymes and causes a 3 -4-fold increase in Ki for catecholamine inhibitors [12].…”
Section: Discussionmentioning
confidence: 99%